N-cadherin knockdown leads to disruption of trophoblastic and endothelial cell interaction in a 3D cell culture model – New insights in trophoblast invasion failure. Issue 3 (4th May 2018) - Multhaup, A.; Huppertz, B.; Göhner, C.; Böhringer, M.; Mai, M.; Markert, U.; Schleußner, E.; Groten, T.
ABSTRACT: Introduction : Trophoblast homing to maternal spiral arteries is mandatory for successful placentation. Cell-cell adhesion molecules regulate this process and adhesion molecule expression is altered in impaired placentation. We hypothesize that, similar to immune cell recruitment, trophoblast cell adherence and rolling are primarily mediated by adhesion molecules like, cadherins, immunoglobulins, selectins and their partnering ligands. Here, the interdependence of adhesion molecule expression in trophoblastic cell lines of diverse origin was investigated in relation to their interaction with endothelial cell networks on Matrigel® co-cultures and the effect of specific adhesion molecule knockdown analyzed. Methods : Trophoblastic cells were labeled in red and co-cultured with green HUVEC networks on Matrigel®. Association was quantified after collection of fluorescence microscopy pictures using Wimasis® internet platform and software. Expression of adhesion molecules was analyzed by PCR and Western blot, immuno-fluorescence and flow cytometry. The impact of adhesion molecules on trophoblast-endothelial-cell interaction was investigated using siRNA technique. Results : N-cadherin and CD162 were specifically expressed in the trophoblast cell line HTR-8/SVneo, which closely adhere to and actively migrate toward HUVEC networks on Matrigel®. Suppression of N-cadherin led to a significant alteration in trophoblast-endothelial cell interaction. Expression of VE-cadherin in closely interacting trophoblast cells was not confirmed in vitro. Discussion : We identified N-cadherin to mediate specific interaction between HUVEC and the migrating trophoblast cells HTR-8/SVneo in a Matrigel® co-culture model. VE-cadherin contribution could not be confirmed in vitro . Our results support the hypothesis that impaired N-cadherin but not VE-cadherin expression is involved in trophoblast recruitment to the maternal endothelium.